Na powierzchni i pod powierzchnią malatury — kryteria przezroczystości obrazu - Karapuda, Arkadiusz (Załącznik Kulturoznawczy, 2018)
Should the artistic activity be understood as a reflection of the world or maybe a semi-transparent veil in front of the eyes of dilettantes, which is removed without their knowledge and will only serve for special occasions? The phenomenon of transparency accompanies humans from their first glimpse on the surface of a frozen lake. In case of visual arts, it refers both to the visible aspects of an artwork which result from its plastic form and to its intended intellectual features which impact its meaning. Individual nature of painting makes this field of art not entirely transparent, not entirely understandable, inaccessible for dilettantes and demanding effort from its recipient. Having in mind the thesis about not full transparency of the painting medium, one can say that it is the surface of the paint that enables to unite form and content of a painting, therefore, it is worth to remember the role of the surface, which in this case has the key meaning.